"Der belgische Symbolismus - Interview mit dem Direktor der Alten Nationalgalerie, Dr. Ralph Gleis" (PODCAST) - Huybrechts, Yves

"Gebaute Träume - Wohnkultur in Flandern und Wallonien" (VIDEO) - Huybrechts, Yves

Geflippte E-Tutor*innenschulungen - Neiske, Iris (Inverted Classroom and beyond 2021 10 Jahre #icmbeyond. Norderstedt)

Building, emptying out, or dreaming? Action structures and space in undergraduates’ metaphors of academic writing - Scharlau, Ingrid; Karsten, Andrea; Rohlfing, Katharina (Journal of Writing Research)
The aim of the present study is to bring new momentum into research on students’ understanding of academic writing. Drawing on the idea that metaphors give insight into implicit conceptions of abstract entities and processes, we developed a detailed and differentiated set of conceptual metaphors that can be used to study student ideas about writing in research, teaching, and interventions. A large sample of undergraduates produced their everyday understanding of writing in short texts beginning with a self-generated metaphor. Based on theories from cognitive linguistics, the conceptual metaphors in their texts were analyzed in terms of their action quality (transitivity) and spatiality (spatial primitives). The undergraduates’ conceptualizations were very heterogeneous. Most metaphors depart strongly from scientific approaches to academic writing within cognitive psychology and sociocultural theory. Roughly half of the metaphors could be collated to one of four metaphor systems. Depending on the desired degree of abstraction or concreteness, conceptual metaphors or metaphor systems can be employed in further studies to illuminate thinking about writing.
Keywords: metaphor analysis; academic writing; transitivity; spatial primitives

Grenzüberschreitung und Distanzierung – Geschlechterforschung in universitären Toiletten - Krollmann, Rabea; Schmidt, Rebecca; Spill, Annika (blog interdisziplinäre geschlechterforschung)

Das Stellarium Gornergrat - Hohmann, Sascha; Gschwind, Stéphane; Müller, Andreas; Nordine, Jeffrey; Riesen, Timm-Emanuel (PhyDid B)

Stellarium Gornergrat – A swiss robotic Observatory for Education and Citizen Science - Ekström, Sylvia; Frey, Jonas; Gschwind, Stéphane; Hohmann, Sascha; Müller, Andreas; Riesen, Timm-Emanuel; Ruffieux, Simon; Schlatter, Peter (SPG-Mitteilungen)

Kinder- und Jugendliteratur intermedial. Unterrichtsanregungen und -materialien zum literarischen Lernen im Medienverbund anhand von Emil und die Detektive (Gym/Ge) und Jakob der Lügner (BK); erstellt von Masterstudierenden der Universität Paderborn

Investigations for the Optimization of Visual and Geometrical Properties of Arburg Plastic Freeforming Components - Moritzer, Elmar; Hecker, Felix; Elsner, Christian Lennart; Hirsch, André (Proceedings: 2021 Annual International Solid Freeform Fabrication Symposium (SFF Symp 2021))
Arburg Plastic Freeforming (APF) is an additive manufacturing process with which three-dimensional, thermoplastic components can be produced layer by layer. Visual and geometrical properties are a major criterion for characterizing the resulting component quality. The aim of this study was to investigate the influences on visual and geometrical properties of APF components depending on process parameters. Initially the focus was on the analysis of the shrinkage behavior of ABS-M30 (Stratasys). On the basis of the results and an existing procedure by the machine manufacturer, an optimized procedure for determining the scaling factors was developed to counteract the shrinkage. With this procedure a higher dimensional accuracy of the components can be achieved. In addition, it was investigated whether an adaption of the form factor based on a mathematical model depending on the component geometry makes sense. The results were transferred into manufacturing guidelines, which allow the user of the APF-technology to optimize process parameters more efficiently.

Comparison of Component Properties and Economic Efficiency of the Arburg Plastic Freeforming and Fused Deposition Modeling - Moritzer, Elmar; Hecker, Felix; Driediger, Christine; Hirsch, André (Proceedings: 2021 Annual International Solid Freeform Fabrication Symposium (SFF Symp 2021))
The additive manufacturing process Fused Deposition Modeling (FDM) is established in the industry for many years. A new, similar process to FDM is the Arburg Plastic Freeforming (APF). The main differences between both processes are the form of the starting material (FDM: Filaments, APF: Conventional granulate) and the material deposition during the layer formation (FDM: Melt strand, APF: fine molten droplets). Since the two processes can be used in similar applications, the aim of this study is to compare both processes in a holistic way. Furthermore, the advantages and disadvantages of the processes are to be highlighted. The systematic comparison between a Stratasys 400mc and the Freeformer 200-3X is divided into the areas of component properties, design limitations and economic efficiency. The material ABS-M30 (Stratasys) is used in both processes. The results show comparable component properties regarding mechanical and optical properties but also differences in design limitations and cost efficiency.

Investigation and Modeling of the Residence Time Dependent Material Degradation in the Arburg Plastic Freeforming - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Proceedings: 2021 Annual International Solid Freeform Fabrication Symposium (SFF Symp 2021))
The Arburg Plastic Freeforming (APF) is an additive manufacturing process with which three-dimensional, thermoplastic components can be produced layer by layer. One disadvantage of the APF is the long residence time of the molten material in the plasticizing unit compared to conventional injection moulding. The dosing volume is emptied very slowly due to only discharging fine plastic droplets. As a result, long residence times can be expected, which can lead to thermal degradation of the material. The aim of this study was to develop a model for calculating the residence time of the material in the APF. The residence time of the material in the thermally critical dosing volume is predicted using software developed in-house. The accuracy of the model could be verified by experimental investigations. Finally, the thermal degradation of the material was investigated by analyzing the correlation to the mechanical properties of tensile strength specimens.

Denken mit dem Stift?! – Digitale Visualisierungsprozesse als Zugang zu komplexen wirtschafts- und berufspädagogischen Themenfeldern. - Kückmann, Marie-Ann; Kundisch, Heike (Didaktisierung des Digitalen: Zur Entwicklung berufs- und wirtschaftspädagogischer Studiengänge)

Should I Follow this Model? The Effect of Uncertainty Visualization on the Acceptance of Time Series Forecasts - Leffrang, Dirk; Müller, Oliver (IEEE Workshop on TRust and EXpertise in Visual Analytics)

Laser Sintering Design Guidelines for media transmitting Components - Kletetzka, Ivo; Kummert, Christina; Schmid, Hans-Joachim (Proceedings of the 32nd Annual International Solid Freeform Fabrication Symposium)
In automotive and other fields of application media-carrying components often have complex, flow-optimized geometries and are made of plastics for reasons of weight and cost. Therefore, the laser sintering technology is predestinated to manufacture these components as it offers a very high degree of design freedom and good mechanical properties. For industrial applications the long-term properties of the SLS material in contact with liquid media are important and were therefore investigated for PA12, PP and PA613. Hereby, different media such as motor oil or Glysantin based coolant were tested with different temperatures and immersion times of up to 26 weeks. The mechanical properties were tested after immersion and compared to injection molded samples. Furthermore, laser sintering design guidelines for media-carrying components were developed. These guidelines for instance include the minimum wall thickness to ensure media tightness and the removal of powder from channels with a high length to diameter ratio.

Student engagement in digitalen Lehr-Lern-Szenarien - Schmidt, Rebekka; Mindt, Ilka (Hochschule auf Abstand. Ein multiperspektivischer Zugang zur digitalen Lehre)
In diesem Beitrag wird das Konzept des student engagement mit den drei Dimensionen Verhalten, Emotion und Kognition skizziert und in Bezug auf die unterstützenden Faktoren für Lehre auf Distanz in digitalen Lehr-Lernsettings untersucht. Ein Abgleich der theoretischen Grundlagen mit Forschungsergebnissen verschiedener Studien zum Onlinesemester 2020 sowie eine Konkretisierung durch Evaluationen aus Seminaren der englischen Sprachwissenschaft und der Kunstdidaktik gibt Aufschluss darüber, wie ein geeignetes how to engage auch in digitalen Lehr-Lernsettings gelingen kann. Darüber hinaus lassen die Ausführungen erkennen, dass die unterstützenden Faktoren häufig in ähnlich priorisiert werden. Daraus ergibt sich eine Reihenfolge mit dem unterstützenden Umfeld an erster, aktivem und kollaborativem Lernen an zweiter, Erleben von Kompetenz an dritter und akademischer Herausforderung an vierter Stelle. Die Ergebnisse können damit einen Weg aufzeigen, wie auch in ungewohnten Lehr-Lernsettings sukzessive ein geeignetes how to engage entwickelt werden kann, um student engagement zu fördern.

"Unsere Rache ist unsere Existenz. Unsere Waffe ist die Sprache." Zum desintegrativen Potenzial von Mirna Funks Roman "Winternähe" - Spener, Anna Maria (Undercurrents – Forum für linke Literaturwissenschaft)

“Mably on Esteem, Republicanism, and the Question of Human Corruption.” - Blank, Andreas (Journal of Modern Philosophy)

“The Morality of the Desire for Esteem: Gassendi and the Augustinian Challenge.” - Blank, Andreas (History of European Ideas)

“Wolff on Duties of Esteem in the Law of Peoples.” - Blank, Andreas (European Journal of Philosophy)

Die epistemische Dimension der Neuen Rechten. Von einer Kritik des Wissenschafts- und Bildungsverständnisses der Neuen Rechten zu einer Selbstkritik - Haker, Christoph; Otterspeer, Lukas (recht extrem? Dynamiken in zivilgesellschaftlichen Räumen)

Against Latour – On the Questionable Foundations of Post-Critical Pedagogy - Haker, Christoph; Otterspeer, Lukas (On Education. Journal for Research and Debate)
Critique has run out of steam – this diagnosis by Bruno Latour is crucial for the “Manifesto for post-critical education” as well as for the on_education issue “The Fatique of Critique?”. With this essay, we contradict Latour's diagnosis. Latour’s polemic against critique is based firstly on a questionable diagnosis of our time and secondly on a general and programmatic critique of sociology. Against that, we bring out two main points. The first insight highlights that change is initially dependent on variations that can only arise from a negation of the existing. The second insight comes from the sociology of critique, which paradoxically sees success in the failure of critique.

Die Beweglichkeit der Kritik: zur Wechselbeziehung von Kontextualisierung und Objektivierung im digitalen Zeitalter - Haker, Christoph; Otterspeer, Lukas (BEHEMOTH. A Journal on Civilisation)

Digitalisation in the Classroom – Learning Tools - Schneider, Jennifer Nicole (Fostering Digitisation and Industry 4.0: Education – Vocation - Industry – Future. New Opportunities and Challenges for European VET. Insights in the DigI-VET Project)

Fostering Digitisation and Industry 4.0: Education – Vocation – Industry – Future. New Opportunities and Challenges for European VET. Insight in the DigI-VET Project

Higher-rank quantum-classical correspondence - Hilgert, Joachim; Weich, Tobias; Wolf, L.

Medien der Sorge, Techniken des Selbst. Praktiken des Über-sich-selbst-Schreibens bei Christoph Schlingensief und Elfriede Jelinek - Degeling, Jasmin

Hallo Schönheiten! Performances und Aushandlungen der Geschlechterordnung in der YouTube-Beauty-Community - Richter, Susanne
Keywords: {<}3

Weltweite Verfügbarkeit und digitale Langzeitarchivierung - Ried, Dennis (Mitteilungen der IMRG)

Conference Report: Dynamics of Tradition: Islamic Theology and Law in Relation (September 17-19, 2021, Paderborn) - Nassery, Idris; Tatari, Muna; Mustafa, Abdul Rahman

Digitale Prozessintegration in berufs- und wirtschaftspädagogischen Studiengängen – Überlegungen zur Professionalität und professionellen Entwicklung - Jenert, Tobias; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik – online)

Being a first-year student during COVID-19 pandemic - Büker, Ronja (Zeitschrift für Hochschulentwicklung)

Anderssein als Ressource: Habitus und Habitusreflexion in der Lehrer*innenbildung - Jenert, Tobias (PraxisForschungLehrer*innenbildung)
Lehrer*innen können dazu beitragen, dass bestehende soziale Ungleichheiten verstärkt oder auch abgebaut werden. Eine wichtige Rolle spielen dabei der sogenannte Habitus der Lehrer*innen und dessen (Nicht-)Passung zur sozialen Herkunft der Schüler*innen. In diesem Text stelle ich die Frage, wie angehende Lehrer*innen im Studium unterstützt werden können, die Bedeutung eigener habitueller Prägungen für das professionelle Handeln als Lehrperson zu reflektieren. Ganz besonders befasse ich mich mit der Rolle der Lehrer*innenbildner*innen bei der Förderung von solchen habitusreflexiven Kompetenzen. Hier spielen das Selbst der Hochschullehrenden und die bildungsbiographischen Erfahrungen, die auf dem Weg in die Hochschule gemacht wurden, eine wichtige Rolle.

Lehrentwicklung an Hochschulen als transferorientierte Netzwerkarbeit: Das Bündnis für Hochschullehre Lehren - Jenert, Tobias; Bosse, Elke (Transfer von Innovation und Wissen)

The interplay of personal and contextual diversity during the first year at Higher Education: Combining a quantitative and a qualitative approach - Jenert, Tobias; Brahm, Taiga (Frontline Learning Research)
Research on student transition into Higher Education (HE) has taken different theoretical perspectives. First, studies investigated personal variables such as students´ self-efficacy, emotions and motivation regarding the transition from school to HE. A second strand of research focused on contextual variables, for instance college effectiveness research. With this paper, we combine both the personal and the contextual approach. We aim to investigate the interaction between personal and contextual diversity during the transition into HE, taking into account students’ diversity in particular with regard to gender and individual characteristics, such as self-efficacy. We explored the heterogeneity in students’ personal characteristics by conducting a latent profile analysis (LPA) based on students’ intrinsic motivation, self-efficacy and anxiety before entering Higher Education. LPA resulted in three distinct profiles, with significant differences in how students perceived the first year. This finding suggests that students’ personal characteristics when entering Higher Education influence how they experience the study environment. To investigate the interplay between individual and contextual differences in more detail, we conducted a qualitative longitudinal study with 14 first-year students in parallel with the panel survey. We found that individual students react very differently to specific characteristics and events of the first-year environment. Our study adds to the growing body of research that aims to grasp the complexity of interactions between individual and contextual differences. Specifically, we illustrate how combining quantitative and qualitative methods can provide new insights into person-context interactions.
Keywords: Education

Ein modellbasiertes Messverfahren zur Charakterisierung von Piezokeramiken unter Verwendung eines einzelnen scheibenförmigen Probekörpers - Feldmann, Nadine
Designprozesse von Schallwandlern werden durch zunehmende Rechenkapazitäten immer mehr durch simulative Betrachtungen unterstützt. Dabei ist vor allem die Wahl der Materialparameter der verwendeten Materialien wichtig für ein realitätsnahes Simulationsergebnis. Bei Schallwandlern werden häufig Piezokeramiken als aktive Elemente genutzt, welche sich durch eine Verkopplung mechanischer und elektrischer Eigenschaften auszeichnen. Zur Bestimmung ihrer Materialparameter stellt der IEEE Standard on Piezoelectricity ein standardisiertes Verfahren dar. Dazu sind fünf Impedanzmessungen an vier unterschiedlich gefertigten Probekörpergeometrien notwendig. Da an jedem einzelnen Probekörper nur eine Untermenge aller notwendigen Materialparameter bestimmt werden kann, werden diese dann zu einem kompletten Materialparametersatz zusammengefügt. Aufgrund der unterschiedlichen Prozessbedingungen, bei denen die jeweiligen Probekörper hergestellt werden, ist dieser Materialparametersatz jedoch inkonsistent und kann nie das Verhalten einer einzelnen Probe beschreiben. Daher wird in der vorliegenden Arbeit ein Messverfahren entwickelt, mit dem es möglich ist, alle relevanten Materialparameter unter besonderer Berücksichtigung von Dämpfung an einem einzelnen Probekörper allein durch Impedanzmessungen zu bestimmen. Als Probekörper wird dazu eine in der Anwendung häufig verwendete Scheibengeometrie verwendet. Um eine hinreichend hohe Sensitivität auf alle Materialparameter zu gewährleisten, wird diese mit einer optimierten Elektrodentopologie gefertigt. Da in diesem Fall keine analytische Betrachtung mehr möglich ist, wird das Messverfahren durch einen inversen Ansatz realisiert.

Betriebliche Weiterbildungskulturen in Zeiten der Digitalisierung – Eine Analyse mit Daten des BIBB-Qualifizierungspanels. - Krause, Ina; Gerhards, Christian (Internationales Jahrbuch für Erwachsenenbildung 2022: Optimierung in der Weiterbildung)

Is Consistency the Panacea? Inconsistent or Consistent Tax Transfer Prices with Strategic Taxpayer and Tax Authority Behavior - Diller, Markus; Lorenz, Johannes; Schneider, Georg; Sureth-Sloane, Caren

The Tax Complexity Index – A Survey-Based Country Measure of Tax Code and Framework Complexity - Hoppe, Thomas; Schanz, Debora; Sturm, Susann; Sureth-Sloane, Caren
This paper introduces an index that captures the complexity of countries’ corporate income tax systems faced by multinational corporations. It is based on surveys of highly experienced tax consultants of the largest international tax services networks. The index, called the Tax Complexity Index (TCI), is composed of a tax code subindex covering tax regulations and a tax framework subindex covering tax processes and features. For a sample of 100 countries for the year 2016, we find that the level of tax complexity varies considerably across countries, while tax code and framework complexity also vary within countries. From a global perspective, tax complexity is strongly driven by the complexity of both transfer pricing regulations in the tax code and tax audits in the tax framework. When analyzing the associations with other country characteristics, we identify different correlation patterns. For example, tax framework complexity is negatively associated with countries’ governance, suggesting that strongly governed countries tend to have less complex tax frameworks, while tax code complexity is positively associated with the statutory tax rate, indicating that high-tax countries tend to have more complex tax codes. However, none of the observed associa-tions are very strong. We conclude that tax complexity represents a distinct country charac-teristic and propose the use of our TCI and its subindices in future research.

Banks’ tax disclosure, financial secrecy, and tax haven heterogeneitys - Eberhartinger, Eva; Speitmann, Raffael; Sureth-Sloane, Caren
This study investigates the effect of mandatory public Country-by-Country Reporting (CbCR) for European banks on their presence in tax and regulatory havens. We find that the number of subsidiaries of European banks in tax havens declines significantly after the introduction of mandatory public CbCR in contrast to insurance firms that need not disclose. We document that this decline is mainly driven by a reduction of subsidiaries in small countries with little economic substance (“dot havens”) and in tax havens that are regulatory havens at the same time, i.e., with high financial secrecy. Further, we find that high exposure to reputational risk is a major amplifier of reorganizational activities. Our results explain prior mixed evidence and document that CbCR effectively curbs tax haven presence only under specific circumstances, i.e., in countries offering both tax shelter and financial secrecy, and more strongly for banks with high reputational risk. These findings suggest that increased tax disclosure on banks does not effectively attenuate tax haven presence per se, but only for a subset of havens and banks. Policymakers need to be aware of these limitations, especially in light of the current decision of extending public CbCR to all large multinationals.

Are Risk-based Tax Audit Strategies Rewarded? An Analysis of Corporate Tax Avoidance - Eberhartinger, Eva; Safaei, Reyhaneh; Sureth-Sloane, Caren; Wu, Yuchen (TRR 266 Accounting for Transparency Working Paper Series No. 60, WU International Taxation Research Paper Series No. 2021-07)

Is Transfer Pricing Harmonization the Panacea? Reporting Transparency, Standards Consistency, and Tax Avoidance - Diller, Markus; Lorenz, Johannes; Schneider, Georg Thomas; Sureth-Sloane, Caren

The Epidemiology of Tax Avoidance Narratives - Lorenz, Johannes; Diller, Markus; Sureth-Sloane, Caren

Identification of joints for a load-adapted shape in a body in white using steady state vehicle simulations - Martin, Sven; Schütte, Jan; Bäumler, C.; Sextro, Walter; Tröster, Thomas (Forces in Mechanics)

Tire Wear Reduction Based on an Extended Multibody Rear Axle Model - Schütte, Jan; Sextro, Walter (Vehicles)
To analyze the influence of suspension kinematics on tire wear, detailed simulation models are required. In this study, a non-linear, flexible multibody model of a rear axle system is built up in the simulation software MSC Adams/View. The physical model comprises the suspension kinematics, compliance, and dynamics as well as the non-linear behavior of the tire using the FTire model. FTire is chosen because it has a separate tire tread model to compute the contact pressure and friction force distribution in the tire contact patch. To build up the simulation model, a large amount of data is needed. Bushings, spring, and damper characteristics are modeled based on measurements. For the structural components (e.g., control arms), reverse engineering techniques are used. The components are 3D-scanned, reworked, and included as a modal reduced finite element (FE)-model using component mode synthesis by Craig–Bampton. Finally, the suspension model is validated by comparing the simulated kinematic and compliance characteristics to experimental results. To investigate the interaction of suspension kinematics and tire wear, straight line driving events, such as acceleration, driving with constant velocity, and deceleration, are simulated with different setups of wheel suspension kinematics. The influence of the setups on the resulting friction work between tire and road is examined, and an exemplarily calculation of tire wear based on a validated FTire tire model is carried out. The results demonstrate, on the one hand, that the chosen concept of elasto-kinematic axle leads to a relatively good match with experimental results and, on the other hand, that there are significant possibilities to reduce tire wear by adjusting the suspension kinematics.

Kompetenzförderung im Laborpraktikum - Sacher, Marc; Bauer, Anna (Labore in der Hochschullehre. Didaktik, Digitalisierung, Organisation)

Studentische Akzeptanz und Relevanzwahrnehmung eines disziplinspezifischen Workshops „Wissenschaftliche Vorträge in der Physik“ - Bauer, Anna; Sacher, Marc; Brassat, Katharina (hochschullehre)

Entwicklung eines Bewertungsmodells zur handlungsorientierten Messung experimenteller Kompetenz (Physik)Studierender - Bauer, Anna; Reinhold, Peter; Sacher, Marc (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung)

Bewertungsmodell zur experimentellen Performanz (Physik)Studierender - Bauer, Anna; Reinhold, Peter; Sacher, Marc (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen)

Überlegungen auf dem Weg zu einer Theorie lehrbezogenen Wandels an Hochschulen - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Die Frage, wie sich die Weiterentwicklung der Lehre an Hochschulen systematisch verankern lässt, erfährt mit dem Auslaufen von Förderprogrammen wie dem QPL erneute Aufmerksamkeit. Bislang fehlt es an einer kontextspezifischen Theorie, die lehrbezogenen Wandel an Hochschulen analysier- und gestaltbar macht. In jedem Fall sind Change-Konzepte aus dem betriebswirtschaftlichen Bereich nur sehr beschränkt auf Hochschulen übertragbar. Demgegenüber gibt neuere Forschung Hinweise darauf, welche Kernkategorien eine hochschulspezifische Change- Theorie umfassen könnte. Darauf aufbauend schlägt der Beitrag zwei Konzepte als Kernkategorien einer Theorie lehrbezogenen Wandels an Hochschulen vor.
Keywords: educational development; change management; educational innovation

Towards a Scalable and Flexible Simulation and Testing Environment Toolbox for Intelligent Microgrid Control - Bode, Henrik; Heid, Stefan Helmut; Weber, Daniel; Hüllermeier, Eyke; Wallscheid, Oliver (arXiv:2005.04869)
Micro- and smart grids (MSG) play an important role both for integrating renewable energy sources in conventional electricity grids and for providing power supply in remote areas. Modern MSGs are largely driven by power electronic converters due to their high efficiency and flexibility. Nevertheless, controlling MSGs is a challenging task due to highest requirements on energy availability, safety and voltage quality within a wide range of different MSG topologies. This results in a high demand for comprehensive testing of new control concepts during their development phase and comparisons with the state of the art in order to ensure their feasibility. This applies in particular to data-driven control approaches from the field of reinforcement learning (RL), whose stability and operating behavior can hardly be evaluated a priori. Therefore, the OpenModelica Microgrid Gym (OMG) package, an open-source software toolbox for the simulation and control optimization of MSGs, is proposed. It is capable of modeling and simulating arbitrary MSG topologies and offers a Python-based interface for plug & play controller testing. In particular, the standardized OpenAI Gym interface allows for easy RL-based controller integration. Besides the presentation of the OMG toolbox, application examples are highlighted including safe Bayesian optimization for low-level controller tuning.

ProConAR: A Tool Support for Model-based AR Product Configuration - Gottschalk, Sebastian; Yigitbas, Enes; Schmidt, Eugen; Engels, Gregor (Human-Centered Software Engineering. HCSE 2020)
Mobile shopping apps have been using Augmented Reality (AR) in the last years to place their products in the environment of the customer. While this is possible with atomic 3D objects, there is is still a lack in the runtime conﬁguration of 3D object compositions based on user needs and environmental constraints. For this, we previously developed an approach for model-based AR-assisted product conﬁguration based on the concept of Dynamic Software Product Lines. In this demonstration paper, we present the corresponding tool support ProConAR in the form of a Product Modeler and a Product Conﬁgurator. While the Product Modeler is an Angular web app that splits products (e.g. table) up into atomic parts (e.g. tabletop, table legs, funnier) and saves it within a conﬁguration model, the Product Conﬁgurator is an Android client that uses the conﬁguration model to place diﬀerent product conﬁgurations within the environment of the customer. We show technical details of our ready to use tool-chain ProConAR by describing its implementation and usage as well as pointing out future research directions.
Keywords: Product Configuration; Augmented Reality; Model-based; Tool Support

Every Node for Itself: Fully Distributed Service Coordination - Schneider, Stefan Balthasar; Klenner, Lars Dietrich; Karl, Holger (IEEE International Conference on Network and Service Management (CNSM))
Modern services consist of modular, interconnected components, e.g., microservices forming a service mesh. To dynamically adjust to ever-changing service demands, service components have to be instantiated on nodes across the network. Incoming flows requesting a service then need to be routed through the deployed instances while considering node and link capacities. Ultimately, the goal is to maximize the successfully served flows and Quality of Service (QoS) through online service coordination. Current approaches for service coordination are usually centralized, assuming up-to-date global knowledge and making global decisions for all nodes in the network. Such global knowledge and centralized decisions are not realistic in practical large-scale networks. To solve this problem, we propose two algorithms for fully distributed service coordination. The proposed algorithms can be executed individually at each node in parallel and require only very limited global knowledge. We compare and evaluate both algorithms with a state-of-the-art centralized approach in extensive simulations on a large-scale, real-world network topology. Our results indicate that the two algorithms can compete with centralized approaches in terms of solution quality but require less global knowledge and are magnitudes faster (more than 100x).
Keywords: distributed management; service coordination; network coordination; nfv; softwarization; orchestration

Self-Driving Network and Service Coordination Using Deep Reinforcement Learning - Schneider, Stefan Balthasar; Manzoor, Adnan; Qarawlus, Haydar; Schellenberg, Rafael; Karl, Holger; Khalili, Ramin; Hecker, Artur (IEEE International Conference on Network and Service Management (CNSM))
Modern services comprise interconnected components, e.g., microservices in a service mesh, that can scale and run on multiple nodes across the network on demand. To process incoming traffic, service components have to be instantiated and traffic assigned to these instances, taking capacities and changing demands into account. This challenge is usually solved with custom approaches designed by experts. While this typically works well for the considered scenario, the models often rely on unrealistic assumptions or on knowledge that is not available in practice (e.g., a priori knowledge). We propose a novel deep reinforcement learning approach that learns how to best coordinate services and is geared towards realistic assumptions. It interacts with the network and relies on available, possibly delayed monitoring information. Rather than defining a complex model or an algorithm how to achieve an objective, our model-free approach adapts to various objectives and traffic patterns. An agent is trained offline without expert knowledge and then applied online with minimal overhead. Compared to a state-of-the-art heuristic, it significantly improves flow throughput and overall network utility on real-world network topologies and traffic traces. It also learns to optimize different objectives, generalizes to scenarios with unseen, stochastic traffic patterns, and scales to large real-world networks.
Keywords: self-driving networks; self-learning; network coordination; service coordination; reinforcement learning; deep learning; nfv

Detection of high codimensional bifurcations in variational PDEs - Kreusser, Lisa Maria; McLachlan, Robert I; Offen, Christian (Nonlinearity)

Analysis of Hamiltonian boundary value problems and symplectic integration - Offen, Christian
Ordinary differential equations (ODEs) and partial differential equations (PDEs) arise in most scientific disciplines that make use of mathematical techniques. As exact solutions are in general not computable, numerical methods are used to obtain approximate solutions. In order to draw valid conclusions from numerical computations, it is crucial to understand which qualitative aspects numerical solutions have in common with the exact solution. Symplecticity is a subtle notion that is related to a rich family of geometric properties of Hamiltonian systems. While the effects of preserving symplecticity under discretisation on long-term behaviour of motions is classically well known, in this thesis (a) the role of symplecticity for the bifurcation behaviour of solutions to Hamiltonian boundary value problems is explained. In parameter dependent systems at a bifurcation point the solution set to a boundary value problem changes qualitatively. Bifurcation problems are systematically translated into the framework of classical catastrophe theory. It is proved that existing classification results in catastrophe theory apply to persistent bifurcations of Hamiltonian boundary value problems. Further results for symmetric settings are derived. (b) It is proved that to preserve generic bifurcations under discretisation it is necessary and sufficient to preserve the symplectic structure of the problem. (c) The catastrophe theory framework for Hamiltonian ODEs is extended to PDEs with variational structure. Recognition equations for A-series singularities for functionals on Banach spaces are derived and used in a numerical example to locate high-codimensional bifurcations. (d) The potential of symplectic integration for infinite-dimensional Lie-Poisson systems (Burgers’ equation, KdV, fluid equations, . . . ) using Clebsch variables is analysed. It is shown that the advantages of symplectic integration can outweigh the disadvantages of integrating over a larger phase space introduced by a Clebsch representation. (e) Finally, the preservation of variational structure of symmetric solutions in multisymplectic PDEs by multisymplectic integrators on the example of (phase-rotating) travelling waves in the nonlinear wave equation is discussed.

A Novel Higher-order Weisfeiler-Lehman Graph Convolution - Damke, Clemens; Melnikov, Vitaly; Hüllermeier, Eyke (Proceedings of the 12th Asian Conference on Machine Learning (ACML 2020))
Current GNN architectures use a vertex neighborhood aggregation scheme, which limits their discriminative power to that of the 1-dimensional Weisfeiler-Lehman (WL) graph isomorphism test. Here, we propose a novel graph convolution operator that is based on the 2-dimensional WL test. We formally show that the resulting 2-WL-GNN architecture is more discriminative than existing GNN approaches. This theoretical result is complemented by experimental studies using synthetic and real data. On multiple common graph classification benchmarks, we demonstrate that the proposed model is competitive with state-of-the-art graph kernels and GNNs.
Keywords: graph neural networks; Weisfeiler-Lehman test; cycle detection

Argument from Old Man's View: Assessing Social Bias in Argumentation - Spliethöver, Maximilian; Wachsmuth, Henning (Proceedings of the 7th Workshop on Argument Mining (ArgMining 2020))

Spannungszustandsabhängige Schädigungsmodellierung zum Halbhohlstanznieten - Otroshi, Mortaza; Meschut, Gerson (Umformtechnik Blech Rohre Profile)

Platform-independent Reputation and Qualification System for Crowdwork - Hemsen, Paul; Hesse, Marc; Löken, Nils; Nouri, Zahra (2nd Crowdworking Symposium)

Monocular Depth Estimation via Listwise Ranking using the Plackett-Luce model - Lienen, Julian; Hüllermeier, Eyke (arXiv:2010.13118)
In many real-world applications, the relative depth of objects in an image is crucial for scene understanding, e.g., to calculate occlusions in augmented reality scenes. Predicting depth in monocular images has recently been tackled using machine learning methods, mainly by treating the problem as a regression task. Yet, being interested in an order relation in the first place, ranking methods suggest themselves as a natural alternative to regression, and indeed, ranking approaches leveraging pairwise comparisons as training information ("object A is closer to the camera than B") have shown promising performance on this problem. In this paper, we elaborate on the use of so-called listwise ranking as a generalization of the pairwise approach. Listwise ranking goes beyond pairwise comparisons between objects and considers rankings of arbitrary length as training information. Our approach is based on the Plackett-Luce model, a probability distribution on rankings, which we combine with a state-of-the-art neural network architecture and a sampling strategy to reduce training complexity. An empirical evaluation on benchmark data in a "zero-shot" setting demonstrates the effectiveness of our proposal compared to existing ranking and regression methods.

Nonlinear dielectric properties of random paraelectric-dielectric composites - Myroshnychenko, Viktor; Smirnov, Stanislav; Jose, Pious Mathews Mulavarickal; Brosseau, Christian; Förstner, Jens (Acta Materialia)
The challenge of designing new tunable nonlinear dielectric materials with tailored properties has attracted an increasing amount of interest recently. Herein, we study the effective nonlinear dielectric response of a stochastic paraelectric-dielectric composite consisting of equilibrium distributions of circular and partially penetrable disks (or parallel, infinitely long, identical, partially penetrable, circular cylinders) of a dielectric phase randomly dispersed in a continuous matrix of a paraelectric phase. The random microstructures were generated using the Metropolis Monte Carlo algorithm. The evaluation of the effective permittivity and tunability were carried out by employing either a Landau thermodynamic model or its Johnson’s approximation to describe the field-dependent permittivity of the paraelectric phase and solving continuum-electrostatics equations using finite element calculations. We reveal that the percolation threshold in this composite governs the critical behavior of the effective permittivity and tunability. For microstructures below the percolation threshold, our simulations demonstrate a strong nonlinear behaviour of the field-dependent effective permittivity and very high tunability that increases as a function of dielectric phase concentration. Above the percolation threshold, the effective permittivity shows the tendency to linearization and the tunability dramatically drops down. The highly reduced permittivity and extraordinarily high tunability are obtained for the composites with dielectric impenetrable disks at high concentrations, in which the triggering of the percolation transition is avoided. The reported results cast light on distinct nonlinear behaviour of 2D and 3D stochastic composites and can guide the design of novel composites with the controlled morphology and tailored permittivity and tunability.

Die Anbahnung einer forschenden Grundhaltung im Praxissemester – eine empirische Analyse von Bedingungen und Entwicklungsverläufen - Homt, Martina

Der digitale Fußabdruck, Schatten oder Zwilling von Maschinen und Menschen - Engels, Gregor (Gruppe. Interaktion. Organisation. Zeitschrift für Angewandte Organisationspsychologie (GIO))

Tax Misperception and Its Effects on Decision Making - a Literature Review - Blaufus, Kay; Chirvi, Malte; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren
Previous accounting research shows that taxes affect decision making by individuals and firms. Most studies assume that agents have an accurate perception regarding their tax burden. However, there is a growing body of literature analyzing whether taxes are indeed perceived correctly. We review 127 studies on the measurement of tax misperception and its behavioral implications. The review reveals that many taxpayers have substantial tax misperceptions that lead to biased decision making. We develop a Behavioral Taxpayer Response Model on the impact of provided tax information on tax perception. Besides individual traits, characteristics of the tax information and the decision environment determine the extent of tax misperception. We discuss opportunities for future research and methodological limitations. While there is much evidence on tax misperception at the individual level, we hardly find any research at the firm level. Little is known about the real effects of managers’ tax misperception and on how tax information is strategically managed to impact stakeholders. This research gap is surprising as a large part of the accounting literature analyzes decision making and disclosure of firms. We recommend a mixed-method approach combining experiments, surveys, and archival data analyses to improve the knowledge on tax misperception and its consequences.

2018/2019 Umfrage zur Steuerkomplexität in deutschen Finanzverwaltungen - Bornemann, Tobias; Schipp, Adrian; Sureth-Sloane, Caren

Real Effects of Public Country-by-Country Reporting and the Firm Structure of European Banks - Eberhartinger, Eva; Speitmann, Raffael; Sureth-Sloane, Caren
European regulation mandates public country-by-country reporting for banks and is expected to increase reputational costs in case of tax haven activities. We test whether the availability of additional public information on the locations of banks' subsidiaries reduces their tax haven presence. In a preliminary difference-in-difference analysis we find that indeed, tax haven presence in “Dot-Havens” has declined significantly after the introduction of mandatory public country-by-country reporting for European banks, as compared to the insurance industry which is not subject to this regulation.

How Does Trust Affect Concessionary Behavior in Tax Bargaining? - Eberhartinger, Eva; Speitmann, Raffael; Sureth-Sloane, Caren
We analyze the impact of trust on bargaining behavior between auditor and auditee in a tax setting. We study the effect of interpersonal trust and trust in government on both taxpayer and tax auditor. In an experiment with variation in pairwise trust settings, we find evidence that both kinds of trust affect the bargaining behavior, albeit in different ways. While trust in government increases taxpayers’ tax offers, interpersonal trust may lead to more concessionary behavior of tax auditors moderated by trust in government. Our findings help tax authorities to shape programs to enhance compliance in an atmosphere of trust.

When Do Firms Highlight Their Effective Tax Rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren
This study examines the visibility of the GAAP effective tax rate (ETR) in firms’ financial statements as a distinct disclosure choice. Applying a game-theory disclosure model for voluntary disclosure strategies of firms to a tax setting, we argue that firms face a trade-off in their ETR disclosure decisions. On the one hand, firms have an incentive to enhance their ETR disclosure when the ratio offers shareholders “favourable conditions”, for example in terms of higher expected after-tax cash-flows. On the other hand, the disclosure of a favourable low ETR could attract the attention of tax auditors and the public and ultimately result in disclosure costs. We empirically test disclosure behaviour by examining the relation between disclosure visibility and different ETR conditions that reflect different stakeholder specific costs and benefits. While we find that unfavourable ETR conditions are not highlighted, we observe higher disclosure visibility for favourable ETRs (smooth, close to the industry average, decreasing). Additional analyses reveal that this high visibility is characteristic of firm-years with only moderately decreasing ETRs at usual ETR levels, while extreme ETRs are not highlighted. Interestingly and in contrast to our main results, a subsample of family firms do not seem to highlight favourable ETRs.

Umfrage: Steuerliche Verwaltungskosten, steuerliche Corona-Soforthilfemaßnahmen und Investitionen in der Krise - Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren

Tax Complexity in Australia - A Survey-Based Comparison to the OECD Average - Hoppe, Thomas
This article comprehensively reviews Australia’s corporate income tax complexity as faced by multinational corporations (MNCs) and compares it to the average of the remaining OECD countries. Building on unique survey data, I find that the Australian tax code is considerably more complex than the OECD average, which is mainly due to overly complex anti-avoidance legislation, such as regulations on transfer pricing, general anti-avoidance or controlled foreign corporations (CFC). In contrast, Australia’s tax framework, which covers processes and features such as tax law enactment or tax audits, is close to the OECD average. A more granular analysis yields further interesting insights. For example, excessive details in the tax code and the time between the announcement of a tax law change and its enactment turn out to be serious issues in Australia relative to the remaining OECD countries.

2018 Global MNC Tax Complexity Survey - Hoppe, Thomas; Schanz, Deborah; Schipp, Adrian; Siegel, Felix; Sturm, Susann; Sureth-Sloane, Caren

Measuring Tax Complexity Across Countries: A Survey Study on MNCs - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren
This paper introduces an index that comprehensively measures the complexity of countries’ corporate income tax systems faced by multinational corporations. It builds on surveys of highly experienced tax consultants of the largest international tax services networks. The index, called the Tax Complexity Index (TCI), is composed of a tax code subindex covering tax regulations and a tax framework subindex covering tax processes and features. For a sample of 100 countries, we find that tax complexity varies considerably across countries, and tax code and framework complexity also vary within countries. Among others, tax complexity is strongly driven by the complexity of transfer pricing regulations in the tax code and tax audits in the tax framework. When analyzing the associations with other country characteristics, we identify different patterns. For example, with regard to GDP, we find a positive association with tax code complexity and a negative association with tax framework complexity, suggesting that highly economically developed countries tend to have more complex tax codes and less complex frameworks. Overall, our tax complexity measures can serve as valuable proxies in future research and supportive tools for a variety of firm decisions and national and international tax policy discussions.

The Relation between Tax Complexity and Foreign Direct Investments: Evidence Across Countries - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren; Voget, Johannes
This paper analyzes the association between tax complexity and foreign direct investments (FDI) based on the newly developed Tax Complexity Index (TCI) and its components. For a sample of 15,607 new foreign subsidiaries, we find no association between total tax complexity, as proxied by the TCI, and the location probability. When we decompose the TCI into tax code complexity and tax framework complexity, we find opposing associations. Tax code complexity is positively related to the location probability, while tax framework complexity is negatively related to it. These associations are, for example, driven by the complexity of transfer pricing and loss offset regulations in the tax code and the dimensions guidance, audits, as well as filing and payments, in the tax framework. In additional analyses, we find that the associations are sensitive to certain characteristics, such as country-specific and firm-specific characteristics. For example, the positive tax code association diminishes when tax rates are high. Overall, we are the first to provide empirical evidence on potential cost-benefit tradeoffs of tax complexity for FDI and thereby enhance prior literature, which has primarily focused on the costs of tax complexity.

Steuerkomplexität als Standortfaktor. So komplex ist das Steuersystem in Deutschland - Sureth-Sloane, Caren (AWV-Informationen)

Assistive robots in care: Expectations and perceptions of older people - Hoppe, Julia Amelie; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Melkas, Helinä; Tusku, Outi; Pekkarinen, Satu; Hennala, Lea; Thommes, Kirsten (Aging between Participation and Simulation - Ethical Dimensions of Socially Assistive Technologies in elderly care)

All-dielectric silicon metalens for two-dimensional particle manipulation in optical tweezers - Chantakit, Teanchai; Schlickriede, Christian; Sain, Basudeb; Meyer, Fabian; Weiss, Thomas; Chattham, Nattaporn; Zentgraf, Thomas (Photonics Research)

Integration of Novel Sensors and Machine Learning for Predictive Maintenance in Medium Voltage Switchgear to Enable the Energy and Mobility Revolutions - Hoffmann, Martin W.; Wildermuth, Stephan; Gitzel, Ralf; Boyaci, Aydin; Gebhardt, Jörg; Kaul, Holger; Amihai, Ido; Forg, Bodo; Suriyah, Michael; Leibfried, Thomas; Stich, Volker; Hicking, Jan; et al. (Sensors)
The development of renewable energies and smart mobility has profoundly impacted the future of the distribution grid. An increasing bidirectional energy flow stresses the assets of the distribution grid, especially medium voltage switchgear. This calls for improved maintenance strategies to prevent critical failures. Predictive maintenance, a maintenance strategy relying on current condition data of assets, serves as a guideline. Novel sensors covering thermal, mechanical, and partial discharge aspects of switchgear, enable continuous condition monitoring of some of the most critical assets of the distribution grid. Combined with machine learning algorithms, the demands put on the distribution grid by the energy and mobility revolutions can be handled. In this paper, we review the current state-of-the-art of all aspects of condition monitoring for medium voltage switchgear. Furthermore, we present an approach to develop a predictive maintenance system based on novel sensors and machine learning. We show how the existing medium voltage grid infrastructure can adapt these new needs on an economic scale.

Reliable Part-of-Speech Tagging of Historical Corpora through Set-Valued Prediction - Heid, Stefan Helmut; Wever, Marcel Dominik; Hüllermeier, Eyke (Journal of Data Mining and Digital Humanities)
Syntactic annotation of corpora in the form of part-of-speech (POS) tags is a key requirement for both linguistic research and subsequent automated natural language processing (NLP) tasks. This problem is commonly tackled using machine learning methods, i.e., by training a POS tagger on a sufficiently large corpus of labeled data. While the problem of POS tagging can essentially be considered as solved for modern languages, historical corpora turn out to be much more difficult, especially due to the lack of native speakers and sparsity of training data. Moreover, most texts have no sentences as we know them today, nor a common orthography. These irregularities render the task of automated POS tagging more difficult and error-prone. Under these circumstances, instead of forcing the POS tagger to predict and commit to a single tag, it should be enabled to express its uncertainty. In this paper, we consider POS tagging within the framework of set-valued prediction, which allows the POS tagger to express its uncertainty via predicting a set of candidate POS tags instead of guessing a single one. The goal is to guarantee a high confidence that the correct POS tag is included while keeping the number of candidates small. In our experimental study, we find that extending state-of-the-art POS taggers to set-valued prediction yields more precise and robust taggings, especially for unknown words, i.e., words not occurring in the training data.

Sprachtechnologien für Digitale Assistenten - Haeb-Umbach, Reinhold (Studientexte zur Sprachkommunikation: Elektronische Sprachsignalverarbeitung 2020)
Keywords: Poster

Light backscattering from large clusters of densely packed irregular particles - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
We numerically simulate multiple light scattering in discrete disordered media represented by large clusters of irregular non-absorbing particles. The packing density of clusters is 0.5. With such conditions diffuse scattering is significantly reduced and light transport follows propagation channels that are determined by the particle size and topology of the medium. This kind of localization produces coherent backscattering intensity surge and enhanced negative polarization branch if compared to lower density samples.
Keywords: tet_topic_scattering

In-depth Analysis of the Effects of Smart Services on Value Creation - Reinhold, Jannik; Frank, Maximilian; Koldewey, Christian; Dumitrescu, Roman; Buss, Eugen (Proceedings of the ISPIM Connects Bangkok – Partnering for an Innovative Community)

Der ‚Eigene Kalender‘ des Erinnerns: Die Wahrheit der erfundenen Erinnerung in Herta Müllers Romanen, Erzählungen und Essays - Eke, Norbert Otto (German Life and Letters (Special Issue: Herta Müller and the Currents of European History))

GEMINI-Modellierungssprache für Wertschöpfungssysteme - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

GEMINI-Geschäftsmodellmuster-Kartenset - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodellvalidierung - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodell-Roadmapping - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Jointly Optimal Dereverberation and Beamforming - Boeddeker, Christoph; Nakatani, Tomohiro; Kinoshita, Keisuke; Haeb-Umbach, Reinhold (ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Towards a speaker diarization system for the CHiME 2020 dinner party transcription - Boeddeker, Christoph; Cord-Landwehr, Tobias; Heitkaemper, Jens; Zorila, Catalin; Hayakawa, Daichi; Li, Mohan; Liu, Min; Doddipatla, Rama; Haeb-Umbach, Reinhold (Proc. CHiME 2020 Workshop on Speech Processing in Everyday Environments)

Orientierungen in der digitalen Welt

A simplified method for the evaluation of the layer compression test using one 3D digital image correlation system and considering the material anisotropy by the equibiaxial Lankford parameter - Camberg, Alan Adam; Tröster, Thomas

Predicting fracture at non-isothermal forming conditions: A temperature dependent extension of the LS-DYNA GISSMO fracture indicator framework - Camberg, Alan Adam; Erhart, Tobias; Tröster, Thomas

Model-based Product Configuration in Augmented Reality Applications - Gottschalk, Sebastian; Yigitbas, Enes; Schmidt, Eugen; Engels, Gregor (Human-Centered Software Engineering. HCSE 2020)
Augmented Reality (AR) has recently found high attention in mobile shopping apps such as in domains like furniture or decoration. Here, the developers of the apps focus on the positioning of atomic 3D objects in the physical environment. With this focus, they neglect the conﬁguration of multi-faceted 3D object composition according to the user needs and environmental constraints. To tackle these challenges, we present a model-based approach to support AR-assisted product con-ﬁguration based on the concept of Dynamic Software Product Lines. Our approach splits products (e.g. table) into parts (e.g. tabletop, ta-ble legs, funnier) with their 3D objects and additional information (e.g. name, price). The possible products, which can be conﬁgured out of these parts, are stored in a feature model. At runtime, this feature model can be used to conﬁgure 3D object compositions out of the product parts and adapt to user needs and environmental constraints. The beneﬁts of this approach are demonstrated by a case study of conﬁguring modular kitchens with the help of a prototypical mobile-based implementation.
Keywords: Product Configuration; Augmented Reality; Runtime Adaptation; Dynamic Software Product Lines

A Group Signature Scheme from Flexible Public Key Signatures and Structure-Preserving Signatures on Equivalence Classes - Schürmann, Patrick

Kernel-Based Approximation of the Koopman Generator and Schrödinger Operator - Klus, Stefan; Nüske, Feliks; Hamzi, Boumediene (Entropy)
Many dimensionality and model reduction techniques rely on estimating dominant eigenfunctions of associated dynamical operators from data. Important examples include the Koopman operator and its generator, but also the Schrödinger operator. We propose a kernel-based method for the approximation of differential operators in reproducing kernel Hilbert spaces and show how eigenfunctions can be estimated by solving auxiliary matrix eigenvalue problems. The resulting algorithms are applied to molecular dynamics and quantum chemistry examples. Furthermore, we exploit that, under certain conditions, the Schrödinger operator can be transformed into a Kolmogorov backward operator corresponding to a drift-diffusion process and vice versa. This allows us to apply methods developed for the analysis of high-dimensional stochastic differential equations to quantum mechanical systems.

Privacy-Preserving Incentive Systems with Highly Efficient Point-Collection - Bobolz, Jan; Eidens, Fabian; Krenn, Stephan; Slamanig, Daniel; Striecks, Christoph (Proceedings of the 15th ACM Asia Conference on Computer and Communications Security (ASIA CCS ’20),)

Metasurfaces help lasers to mode-lock - Sain, Basudeb; Zentgraf, Thomas (Light: Science & Applications)

Polarization-Encrypted Orbital Angular Momentum Multiplexed Metasurface Holography - Zhou, Hongqiang; Sain, Basudeb; Wang, Yongtian; Schlickriede, Christian; Zhao, Ruizhe; Zhang, Xue; Wei, Qunshuo; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (ACS Nano)

Hypothesis-driven Adaptation of Business Models based on Product Line Engineering - Gottschalk, Sebastian; Rittmeier, Florian; Engels, Gregor (Proceedings of the 22nd IEEE International Conference on Business Informatics)
The continuous innovation of its business models is an important task for a company to stay competitive. During this process, the company has to validate various hypotheses about its business models by adapting to uncertain and changing customer needs effectively and efficiently. This adaptation, in turn, can be supported by the concept of Software Product Lines (SPLs). SPLs reduce the time to market by deriving products for customers with changing requirements using a common set of features, structured as a feature model. Analogously, we support the process of business model adaptation by applying the engineering process of SPLs to the structure of the Business Model Canvas (BMC). We call this concept a Business Model Decision Line (BMDL). The BMDL matches business domain knowledge in the form of a feature model with customer needs to derive hypotheses about the business model together with experiments for validation. Our approach is effective by providing a comprehensive overview of possible business model adaptations and efficient by reusing experiments for different hypotheses. We implement our approach in a tool and illustrate the usefulness with an example of developing business models for a mobile application.
Keywords: Business Model Decision Line; Business Model Adaptation; Hypothesis-driven Adaptation; Software Product Line; Feature Model

Model-based Hypothesis Engineering for Supporting Adaptation to Uncertain Customer Needs - Gottschalk, Sebastian; Yigitbas, Enes; Engels, Gregor (Business Modeling and Software Design)
To build successful products, the developers have to adapt their product features and business models to uncertain customer needs. This adaptation is part of the research discipline of Hypotheses Engineering (HE) where customer needs can be seen as hypotheses that need to be tested iteratively by conducting experiments together with the customer. So far, modeling support and associated traceability of this iterative process are missing. Both, in turn, are important to document the adaptation to the customer needs and identify experiments that provide most evidence to the customer needs. To target this issue, we introduce a model-based HE approach with a twofold contribution: First, we develop a modeling language that models hypotheses and experiments as interrelated hierarchies together with a mapping between them. While the hypotheses are labeled with a score level of their current evidence, the experiments are labeled with a score level of maximum evidence that can be achieved during conduction. Second, we provide an iterative process to determine experiments that offer the most evidence improvement to the modeled hypotheses. We illustrate the usefulness of the approach with an example of testing the business model of a mobile application.
Keywords: Hypothesis Engineering; Model-based; Customer Need Adaptation; Business Model; Product Features

A Holistic Approach to Optimization-Based Design of Hybrid Materials - Triebus, Marcel; Tröster, Thomas (Proceedings 4th International Conference Hybrid Materials & Structures)